2018
DOI: 10.1101/446286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient and reproducible somatic embryogenesis and micro propagation in tomato via novel structures -Rhizoid Tubers

Abstract: 10An improved and highly reproducible system for invitro regeneration via somatic 11 embryogenesis (S.E), applicable to several varieties of tomato (cv. Riogrande, cv. Roma 12 grande, hybrid 17905 and model cv. M82) has been developed. First, we developed a 13 conventional indirect organogenesis for all four varieties used in this study. The 14 cotyledons and hypocotyls of 6-day-old tomato were used as explants (1-2 cm) for callus 15 induction (CI) on different callus induction media (CIM) T 0 -T 12 (6-Benzyla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Surface sterilization of seed explants requires chemicals toxic to microorganisms, but not toxic to seeds, so these chemicals are often required at low concentrations (Bharti et al, 2018). The sterilization method is also one of the things that affect the success rate of seed germination (Saeed et al, 2019). Thus, the sterilization method needs to be optimized because it varies quite a lot depending on the variety of seeds and the conditions of the explants.…”
Section: Germination Of Seeds Into Cotyledonsmentioning
confidence: 99%
“…Surface sterilization of seed explants requires chemicals toxic to microorganisms, but not toxic to seeds, so these chemicals are often required at low concentrations (Bharti et al, 2018). The sterilization method is also one of the things that affect the success rate of seed germination (Saeed et al, 2019). Thus, the sterilization method needs to be optimized because it varies quite a lot depending on the variety of seeds and the conditions of the explants.…”
Section: Germination Of Seeds Into Cotyledonsmentioning
confidence: 99%
“…The production and quality of embryogenic calli has been shown to be influenced by interactions between genotypes and culture conditions [17]. Several studies have reported that plant growth regulator 2, 4-D is the most suitable auxin for callus induction in rice tissue culture [18,19,20,21]. In this study, the effectiveness of different concentrations of 2, 4-D alone was evaluated for callus induction from dehusked seeds of six rice genotypes.…”
Section: Callus Inductionmentioning
confidence: 99%